Effect of parasites on the of digestive system in Iraqi bulbul Pycnonotus lecuotis mesoptamiae - Baghdad Science Journal (مجلة بغداد للعلوم, 2010)
This study included collecting of 150 specimens of the Iraqi Bird Bulbule Pycnonotus lecuotis mesoptamiae (Pycnotidae , Passeriformes), from the 1st of November 2004 to 30th of October 2005 in the city of Baghdad and its suburbs, in concern of identifying the internal parasite of the digestive tract of these birds and studying the diseases resulted from the infection. The study showed that the bird Bulbule is Parasitized by Four types of Cestodes ,two of them are recorded in this kind of bird in Iraq for the first time ,Paradicranotinae anormalis and Haploparaxis sp. , and the other two are Raillietina tetragona and Allohymenolepsis sp. ,and by two types of Pin Worm(Trematode) that are identified for the first time in the Bird Bulbul , Mosesia Chordilesia and Plagiorchis sp. , Gross study showed that the oral cavity ,pharynx and esophagus had no pathological changes in all infected birds .The muscular stomach looked pale ,nearly brown and corroded ,while the mucosa had rottenness and decay in its grooves .The intestinal walls of the infected birds showed spherical ,small size, solid and rough knots and haemorrhgic bruises. some infected birds developed pale and large in size liver . Histological study showed no pathological changes in the oral cavity, pharynx and esophagus of the infected birds. Chronic inflammations and rottenness has been detected in the glandular stomach and the musculae stomach.The villi of the small intestine of the infected birds appeared to have abnormal shapes, cracked and with lost details compared to the control, beside the hypertrophy of the enteric glandular layer. The caecae and the large intestine were healthy for all the examined birds. The study showed also the presence of common lesions in the same organ and other organs of the digestive tract of the same birds, chronic intestinal inflammation, villi atrophy and hypertrophy accompanied the muscular stomach, the liver and pancreatic inflammation for the same bird with the rate of (10.66%).